Unveiling the Policy Paradox: Fertilizer Subsidies and Their Impact on Farmer Welfare in Aceh - Hajad, Vellayati; Ikhsan, Ikhsan; Herizal, Herizal; Setiawan, Deni; Latif, Ikhwan Rahmatika (Jurnal Borneo Administrator, 2024)
This study examines the effectiveness of the fertiliser subsidy program in Aceh Province and its implications for farmer welfare. Although the program seeks to alleviate poverty by reducing production costs and increasing crop yields, the program has yet to yield the expected results. This study employed a qualitative case study approach to analyse the policy's implementation and challenges, focusing on Aceh's unique historical and social context. The study findings reveal that the effectiveness of the policy is hampered by some issues related to resource allocation, communication, administrative governance, and organisational structure. These constraints have prevented the policy from significantly improving the welfare of rice farmers. The study concludes that, although the fertiliser subsidy program has potential, it has not substantially reduced poverty among farmers in Aceh. A significant limitation of this study is its inability to fully assess the potential for increasing government capacity to support farmers due to differences in perceptions and preferences among government actors. This study highlights the need for a more integrated and responsive policy framework to address the unique challenges faced by the agricultural sector in Aceh